Longman preparation course for the TOEFL test - Phillips, Deborah; Lê Huy Lâm (Tp.HCM : Nxb Tp.HCM, 2000)
Listening comprehension; Structure and written expression.
Keywords: Anh ngữ; English language; TOEFL; Anh ngữ -- Luyện thi; English language -- Tests